Pemasangan IP Camera Sebagai Alat Bantu Keamanan Berbasis Jaringan Di Green Mutiara Java Regency - Firdiyan Syah; Feri Febria Laksana; Tri Hastono; Ramdan Harjana; Gunawan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
Currently, there are many security problems that arise in various companies, campuses, and even private homes. These problems can be in the form of theft or robbery, and one way that can be done to anticipate this problem is by using a monitoring camera. Internet Protocol Camera (IP Camera) is an option that is in great demand by the public and even the government because it has major advantages such as reliability, flexibility, and long-term investment. IP Camera is a monitoring camera based on internet protocol. High flexibility allows IP Camera to be applied to wired or wireless networks. This Community Service activity is the installation of an IP Camera at Green Mutiara Java Regency. From the installation results apply Basic Competence to students from team members: 1) Understand the basic concepts of computer and wireless networks; 2) Understand the basic concepts of IP Camera; 3) Understand IP Camera Network configuration; 4) Practicing IP Camera Monitoring Applications and IP Surveillance Features; and 5) Learn about IP Camera security. So that it is obtained that the IP Camera installation has been successful and in accordance with expectations.